Increase of intestinal bacterial sialidase activity exacerbates acute colitis in mice - Hasler, Tobias; Tavares-Gomes, Leticia; Gut, Sereina; Swayambhu, Meghna; Gysi, Mario; Hausmann, Martin; Arora, Natasha; Hennet, Thierry (Frontiers in Molecular Biosciences, 2022)
The availability of endogenous and dietary carbohydrates in the gastrointestinal tract influences the composition of the gut microbiota. Carbohydrate foraging requires the action of bacterially-encoded glycoside hydrolases, which release mono- and oligosaccharides taken up as carbon sources by multiple microbial taxa. In addition to providing nutrients to the microbiota, the cleavage of host glycans by bacterial glycoside hydrolases may alter the properties of surface glycoproteins involved in cell adhesion and activation processes in the gut lumen. To investigate the impact of bacterial glycoside hydrolase activities on the gut microbial composition and on host glycans during colon inflammation, we increased local glycoside hydrolase activity by supplementing mice with recombinant E. coli expressing specific sialidase, fucosidase and rhamnosidase enzymes during acute colitis induced by dextran sulfate sodium ingestion. Whereas increased fucosidase and rhamnosidase activity did not alter the course of colitis, increased sialidase activity exacerbated disease severity. The effect of increased sialidase activity on inflammation was not caused by changes in the microbial composition given that a similar shift in gut bacteria occurred in all groups of mice supplemented with recombinant E. coli. Increased sialidase activity in the colon of treated mice however significantly altered the distribution of sialic acid on mucosal glycans. Treatment of lamina propria dendritic cells with bacterial sialidase also strongly decreased the density of sialylated ligands to anti-inflammatory siglec lectins, indicating that the remodeling of surface sialylation caused by increased sialidase activity likely accounts for the observed exacerbation of acute colitis in mice.